2019
DOI: 10.1177/0363546519825624
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport After Arthroscopic Rotator Cuff Repair: Is There a Difference Between the Recreational and the Competitive Athlete?

Abstract: Background: Return to sport (RTS) remains an important challenge and measure of success for athletes undergoing arthroscopic rotator cuff repair (RCR). Purpose: To determine the rate of RTS after RCR and to analyze predictive factors associated with a lower rate of return. Study Design: Systematic review and meta-analysis. Methods: A systematic review of the literature was performed following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The electronic databases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 26 publications
1
49
0
Order By: Relevance
“…Recent studies by both Altintas et al. 39 and Millett et al. 9 found that despite nearly three-quarters of athletes successfully being able to RTP after their ARCR procedure, approximately 60% of competitive athletes managed to do so at their desired level.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by both Altintas et al. 39 and Millett et al. 9 found that despite nearly three-quarters of athletes successfully being able to RTP after their ARCR procedure, approximately 60% of competitive athletes managed to do so at their desired level.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Thirty-eight percent of the throwing athletes were only able to return to the same level of play or higher after rotator cuff repairs although 79% of the athletes were able to return to play. 1 The occupational ratio of the TMi muscle can be increased as compensational hypertrophy in shoulders with tears in the supraspinatus and IS muscles. 17 In addition, relatively high activity of the TMi muscle was observed during acceleration, deceleration, and follow-through phases of throwing, compared with the activity of IS muscle.…”
Section: Discussionmentioning
confidence: 99%
“…26,35,45 The available literature has mainly demonstrated that most patients successfully return to their preoperative activity level after surgery. [3][4][5]23,24,48 Kim et al 22 performed radiographic assessments to observe how structural integrity influences the time of return to activity. Mihata et al 31 reported the state of tendon healing in active patients but specifically focused on patients who underwent superior capsule reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the published literature concerning active patients has focused on returning to preoperative activities, [3][4][5]24,27,48 and very few radiographic or detailed functional data concentrating on the effect of postoperative activities have been reported. 2,31 Owing to this lack of information, outcome-based guidelines for active patients, in terms of postoperative activity level management, are unavailable.…”
mentioning
confidence: 99%